Measuring External Risks for Peru : Insights from a Macroeconomic Model for a Small Open and Partially Dollarized Economy - Han, Fei (IMF Working Papers; Working Paper, 2014)
This paper quantifies the effects of external risks for Peru, with particular attention to two major external risks, China's investment slowdown and the U.S. monetary policy tightening. In particular, a macroeconomic model for a small open and partially dollarized economy is developed and estimated for Peru to measure the risk spillovers, and simulate domestic macroeconomic responses in different scenarios with these two external risks. The simulation results suggest that Peru's output is vulnerable to both risks, particularly the U.S. monetary policy tightening. Simulations also highlight the importance of higher exchange rate flexiblity and a lower degree of dollarization, which could help mitigate the negative spillover effects of these external risks.